2018
DOI: 10.1002/jtr.2227
|View full text |Cite
|
Sign up to set email alerts
|

Beyond image: Imagined experiences of a destination

Abstract: The aim of this study is to explore the idea that people can imagine themselves in a destination and can have imagined experiences. This broadens our understanding of how people think about destinations and provides an extension of the established destination image literature and that which explores actual tourist experiences. The research involved asking 300 Czech residents who had never been to London to imagine what it would be like to visit. Their responses were examined qualitatively using thematic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Agapito et al (2013) empirically confirmed that the conative image (intention to recommend, intention to revisit, and positive word of mouth) was affected by the cognitive image and affective image in post-visitors. This relationship encourages scholars to show continued interest in how the destination image is formed in non-visitors and how it attracts them to produce an intention to visit the destination (Cherifi et al, 2018) because non-visitors are targets for a destination to explain its tourism marketing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Agapito et al (2013) empirically confirmed that the conative image (intention to recommend, intention to revisit, and positive word of mouth) was affected by the cognitive image and affective image in post-visitors. This relationship encourages scholars to show continued interest in how the destination image is formed in non-visitors and how it attracts them to produce an intention to visit the destination (Cherifi et al, 2018) because non-visitors are targets for a destination to explain its tourism marketing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Destination image is an attitudinal concept held by tourists regarding beliefs, ideas, and impressions of a tourist destination (Crompton, 1979), which is a multi-dimensional construct (Lee and Xue, 2020). Since tourism is an image-driven industry, studying destination image is important in designing effective tourism marketing strategies (Lee and Kim, 2017), especially for potential visitors (Cherifi et al, 2018). Pike (2002) identified the destination image by cognitive and affective components.…”
Section: Destination Imagementioning
confidence: 99%
“…This starting point indicates to us that, from a tourist perspective, it matters that there is, on the one hand, the symbiosis between the intentions related to the attraction and, on the other, between those intentions and the general demand that tourists desire for an attraction to be successful (Ćorluka et al 2021). An essential factor in this context is how the place, with its various attributes, is marketed to the tourists (Cherifi et al 2018). Ward and Gold (1994), Morgan and Pritchard (1999), O´Dell and Billing (2005), and others highlight that it is important for the place to generate a positive image among tourists and that its unique features are foregrounded to be able to create the identity in demand.…”
Section: The Significance Of Placementioning
confidence: 99%
“…Images can convey emotional messages, in turn allowing observers to imagine what the environment provides. When individuals look at a tourism image, they can imagine themselves in the servicescape depicted in the image and can imagine experiences in that environment [43]. When potential consumers see beautiful pictures of natural environments associated with a tourist hotel, their fascination for nature is aroused, and therefore positive emotions toward the hotel are increased [7].…”
Section: The Relationship Between Environmental Clues In Images and W...mentioning
confidence: 99%